Pengaruh Kualitas Pelayanan Terhadap Kepuasan Jemaah Umrah - Jamilatunniswa, Emil; Setiawan, Asep Iwan; Kurniawan, Muhammad Idham; Dasir, Khoirizi H. (Mabrur: Academic Journal of Hajj and Umra, 2024)
The aim of this study was to determine the effect of service quality on the satisfaction of Umrah pilgrims and to determine the level of congregation satisfaction at KBIHU Al-Falah Cicalengka. With a quantitative approach, this study uses primary data collection techniques obtained through distributing questionnaires to Umrah pilgrims and data processed using simple linear regression analysis with a sample size of 30 people. The theory of service quality in this study aims to determine the value of good and bad service quality. The results of this study indicate that the services at KBIHU Al-Falah are good and the level of congregation satisfaction is also very satisfied.